GLUED LAMINATED TIMBER OF PARICÁ REINFORCED WITH SYNTHETIC FIBERS - Rosa, Talitha Oliveira; Terezo, Rodrigo Figueiredo; Mascia, Nilson Tadeu; Righez, João Laryan Borges (Floresta, 2019)
The aim was to evaluate the performance of laminated timber (GLULAM) of Schizolobium parahyba var. amazonicum (paricá) reinforced with fiber of glass or carbon glued with resorcinol adhesive through static bending, shear and tension parallel and perpendicular-to-grain and glued line tests and compare the experimental results with analytical ones. The bending test was divided in 5 treatments (T) composed by 6 test specimens, being T1 the control without fiber reinforcement, T2 with fiberglass of 110 g∙m-2 from grammage, T3 with fiberglass of 200 g∙m-2, T4 with fiberglass of 330 g∙m-2; and T5 with carbon fiber of 200 g∙m-2. The Longitudinal Modulus of Elasticity – MOE of bending test was obtained by analytical and experimental designs. The results were analyzed by Tukey’s test with 5% of significance. There were not a significant increase of the MOE value and the bending strength, of tensile or shear strength in the glued line for all treatments. The analytical design results in displacements significant lower than the experimental. The resorcinol adhesive had a satisfactorily bending performance without ruptures by tension parallel and perpendicular-to-grain or shear.